Cervical cancer screening in rural Bhutan with the careHPV test on self-collected samples: an ongoing cross-sectional, population-based study (REACH-Bhutan). Issue 7 (19th July 2017) - Baussano, Iacopo; Tshering, Sangay; Choden, Tashi; Lazzarato, Fulvio; Tenet, Vanessa; Plummer, Martyn; Franceschi, Silvia; Clifford, Gary M; Tshomo, Ugyen
Abstract : Objectives: The Bhutanese Screening Programme recommends a Pap smear every 3 years for women aged 25–65 years, and coverage ranges from 20% to 60%, being especially challenging in rural settings. The 'REACH-Bhutan' study was conducted to assess the feasibility and outcomes of a novel approach to cervical cancer screening in rural Bhutan. Design: Cross-sectional, population-based study of cervical cancer screening based on the care HPV test on self-collected samples. Setting: Women were recruited in rural primary healthcare centres, that is, Basic Health Units (BHU), across Bhutan. Participants: Overall, 3648 women aged 30–60 were invited from 15 BHUs differing in accessibility, size and ethnic composition of the population. Interventions: Participants provided a self-collected cervicovaginal sample and were interviewed. Samples were tested using care HPV in Thimphu (the Bhutanese capital) referral laboratory. Main outcome measures: Screening participation by geographic area, centre, age and travelling time. Previous screening history and care HPV positivity by selected characteristics of the participants. Results: In April/May 2016, 2590 women (median age: 41) were enrolled. Study participation was 71% and significantly heterogeneous by BHU (range: 31%–96%). Participation decreased with increase in age (81% in women aged 30–39 years; 59% in ≥50 years) and travelling time (90% in women living <30 min from the BHU vs 62% among those >6 hours away). 50% of participants reported no previous screening, with the proportion of never-screened women varying significantly by BHU (range: 2%–72%). 265 women (10%; 95% CI 9% to 11%) were care HPV positive, with a significant variation by BHU (range: 5%–19%) and number of sexual partners (prevalence ratio for ≥3 vs 0–1, 1.55; 95% CI 1.05 to 2.27). Conclusions: Community-based cervical cancer screening by testing self-collected samples for human papillomavirus (HPV) can achieve high coverage in rural Bhutan. However, solutions to bring self-collection, HPV testing and precancer treatment closer to the remotest villages are needed.